1990
DOI: 10.1210/endo-126-6-3232
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Site-Specific Polyclonal Antibodies to c-erbA Peptides Recognizing Human Thyroid Hormone Receptors α1, α2, and β and native 3,5,3′- Triiodothyronine Receptor, and Study of Tissue Distribution of the Antigen

Abstract: The translated products of v-erbA-related cDNAs have been demonstrated to be thyroid hormone receptors, and three different forms of receptor (alpha 1, alpha 2, and beta) have been found in human tissues. We synthesized five peptides corresponding to different portions of these three receptors and raised site-specific polyclonal-antipeptide sera in rabbits. Each antibody displayed high titer and specificity for its respective antigen when tested in an enzyme-linked immunosorbent assay. Each immunoprecipitated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Their results revealed abundant TR 1, TR 2 and TR 1 protein in human hepatocyte. Macchia et al (1990) also Genes with a greater than twofold increase or decrease are shown. The data represent the mean of three independent experiments.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Their results revealed abundant TR 1, TR 2 and TR 1 protein in human hepatocyte. Macchia et al (1990) also Genes with a greater than twofold increase or decrease are shown. The data represent the mean of three independent experiments.…”
Section: Discussionmentioning
confidence: 96%
“…Thereafter, RNA was isolated and cDNA microarray was performed as described in the Materials and Methods. reported equal intensity of 47 kDa (TR 1) and 55 kDa (TR 1) protein bands from rat liver (Macchia et al 1990). Moreover, Flores-Morales et al (2002) used TH 1-deficient mice and cDNA microarray to determine the target genes regulated by T 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone binding Figure 2 Longitudinal sections (original magnification 400) of decalcified rat proximal tibiae, showing immunolocalisation of T 3 R 1 (left panels) and T 3 R 1 (right panels) within distinct zones of the growth plate, using isoform-specific rabbit polyclonal antibodies against human T 3 R 1 and T 3 R 1 proteins (Macchia et al 1990, Falcone et al 1992), which we have demonstrated to recognise rat T 3 R isoforms specifically in bone cells, using western blotting , Bland et al 1997. The upper panels show reserve (RZ), proliferative (PZ) and proximal hypertrophic (HZ) zones; the lower panels show the distal hypertrophic zone (HZ) and metaphyseal primary spongiosum (MPS).…”
Section: Androgen Effects On Growth and Expression Of Its Receptor Inmentioning
confidence: 99%
“…Specific receptor proteins were detected by enhanced chemiluminescent assay (ECL; Amersham) after exposure of filters to X-ray film for 1-20 min. Filters were probed with the following primary antibodies: polyclonal against human T 3 R 1, c-erb A 2 and T 3 R 1 proteins (Macchia et al 1990, Falcone et al 1992, polyclonal against rat RAR (Ali et al 1992), and monoclonal against human VDR (Pike et al 1982) (purchased from Cambridge Research Biochemicals, Zeneca, Northwich, UK). A monoclonal antibody against mouse RXR, which recognises the , and RXR isoforms (4RX 1D12, (Rochette Egly et al 1994)), was used to detect RXR protein.…”
Section: Protein Electrophoresis and Western Blottingmentioning
confidence: 99%
“…There was no change in receptor protein size after induction of cell differentiation by hormones (data not shown). Estimation of the approximate molecular masses of each protein using standard markers indicated that the expressed receptors were of appropriate size (Pike et al 1982, Macchia et al 1990, Ali et al 1992, Falcone et al 1992, Rochette Egly et al 1994. The 4RX 1D12 monoclonal antibody used to detect RXR expression recognises the three RXR isoforms , and (Rochette Egly et al 1994).…”
Section: Receptor Protein Expression and Quantitative Detection In Hlmentioning
confidence: 99%